The impact of cycling on the physical and mental health, and quality of life of people with disabilities: a scoping review - Nina Mosser; Glen Norcliffe; Annika Kruse (Frontiers in Sports and Active Living)
Adaptive cycling holds potential for promoting physical and mental health among individuals with disabilities, who often face barriers to traditional cycling and other forms of exercise. This scoping review systematically examines existing scientific literature to assess the effects of adaptive cycling on the physical and mental health of individuals with disabilities. Following a widely recognized methodological scoping review framework, 35 qualitative and quantitative studies were identified through comprehensive database searches and manual screenings. The review highlights the positive impacts of adaptive cycling on cardiovascular fitness, muscle strength, and overall physical well-being, as well as improvements in mental health and quality of life. Despite these benefits, significant research gaps remain, particularly concerning adaptive cycling modalities, such as sociable cycles, chair transporters, and power-assisted bikes, which were underrepresented in the existing literature. This review underscores the need for further studies to provide a comprehensive understanding on the effects of different adaptive cycling modalities. Such studies are essential to improve accessibility and ultimately support the health and social inclusion of individuals with disabilities.